Macroprudential Policy and Credit Risk in Dual Banking System - Jannatul Liutammima Musta'in; Faaza Fakhrunnas (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2021)
Issues related to financial stability are a very complex problem, especially the global crisis impact in 2008. Based on these conditions, the Basel Committee on Banking Supervision introduced a macroprudential policy to mitigate financial system risk systemically. The study aims to analyze the impact of macroprudential policy on the banks’ risk exposure by adopting credit risk as a risk proxy. By adopting a panel dynamic approach, credit risk is used to be a dependent variable while independent variables consist of the reserve requirement, capital buffer, and a net open position in either conventional and Islamic banks. The observation period starts from 2014 to 2019 with quarterly data, and it involves 22 banks in Indonesia. The study found that macroprudential policy has a long-run relationship to Islamic banks' credit risk but not to conventional banks. The result from Variance Decompositions (VDs) and Impulse Response Factors (IRFs) also showed that each independent variables have an impact to credit risk value in many different directions. According to that, this study suggests that Indonesian financial authority has to pay attention to the different effectiveness and impact of its macroprudential policy, which has to consider the specific characteristics of either conventional or Islamic banks..